2015
DOI: 10.1161/circheartfailure.114.001297
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte p65 Nuclear Factor-κB Is Necessary for Compensatory Adaptation to Pressure Overload

Abstract: Background Nuclear factor kappa B (NF-κB) is often implicated in contributing to the detrimental effects of cardiac injury. This ostensibly negative view of NF-κB competes with its important role in the normal host inflammatory and immune response. We have previously demonstrated that pharmacologic inhibition of NF-κB at the time of acute pressure-overload accelerates the progression of left ventricular hypertrophy (LVH) to heart failure in mice. NF-κB regulates angiogenesis and other factors responsible for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 47 publications
6
13
0
Order By: Relevance
“…Choudhuri et al verified in their study the relationship between NF-κB pathway activation and downstream up-regulation of VEGF in diabetic retinopathy (DR), a microvascular complication of DM, which was in accordance with our findings [21]. And the result was also supported by Polyakova who found that NF-κB inhibition resulted in functional deterioration that was associated with decreased MVD [22]. Furthermore, it was found out that knockout of lncRNA ANRIL combined with PDTC administration resulted in no change in FLK-1 expression but a decrease in FLT-1 expression.…”
Section: Discussionsupporting
confidence: 91%
“…Choudhuri et al verified in their study the relationship between NF-κB pathway activation and downstream up-regulation of VEGF in diabetic retinopathy (DR), a microvascular complication of DM, which was in accordance with our findings [21]. And the result was also supported by Polyakova who found that NF-κB inhibition resulted in functional deterioration that was associated with decreased MVD [22]. Furthermore, it was found out that knockout of lncRNA ANRIL combined with PDTC administration resulted in no change in FLK-1 expression but a decrease in FLT-1 expression.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, IKK/NF‐κB activation in cardiomyocytes caused inflammatory cardiomyopathy and heart failure, while inhibition of NF‐κB signaling by a nondegradable IκBα decreased cardiac hypertrophy and dysfunction induced by Ang II stimuli and pressure overload . Moreover, cardiac NF‐κB regulated angiogenesis and factors responsible for compensatory reaction to transverse aortic constriction–induced intracellular hypoxia, and cardiac‐specific deletion of p65 reduced the hypertrophic response after pressure overload stimulation . Consistently, in our present study, activation of NF‐κB signaling was observed in hypertrophic hearts, and SNIP1 overexpression suppressed the activation.…”
Section: Discussionsupporting
confidence: 90%
“…It is well known that NF‐κB signaling is indispensable for the regulation of various cardiovascular diseases, especially for cardiac hypertrophy, fibrosis, and ventricular remodeling . Nevertheless, the role of NF‐κB signaling in the regulation of cardiac hypertrophy remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Periostin has been recognized as having important role in cardiac development and its pathophysiological mechanisms contributing to CVD. A sufficient evidence has suggested that the periostin plays an important role in coronary artery disease (CAD), hypertension valvular diseases (VHDs), and several cause of cardiac fibrosis …”
Section: Introductionmentioning
confidence: 99%